2002
DOI: 10.1073/pnas.042504299
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide down-regulates brain-derived neurotrophic factor secretion in cultured hippocampal neurons

Abstract: The regulation of neurotrophin (NT) secretion is critical for many aspects of NT-mediated neuronal plasticity. Neurons release NTs by activity-regulated secretion pathways, initiated either by neurotransmitters and͞or by existing NTs by a positive-feedback mechanism. This process depends on calcium release from intracellular stores. Little is known, however, about potential pathways that down-regulate NT secretion. Here we demonstrate that nitric oxide (NO) induces a rapid down-regulation of brain-derived neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 53 publications
6
81
0
7
Order By: Relevance
“…This interpretation is supported by previous experiments in our laboratory, showing that BDNF secretion in hippocampal cultures is rapidly induced by BDNF by means of a mechanism involving TrkB-mediated IP3 formation (23) and subsequent calcium release from intracellular stores (21,23). This positive feedback might persist until counterregulatory mechanisms come into play, such as internalization of TrkB receptors and͞or a reduction of BDNF secretion induced by nitric oxide3protein kinase G signaling (30).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This interpretation is supported by previous experiments in our laboratory, showing that BDNF secretion in hippocampal cultures is rapidly induced by BDNF by means of a mechanism involving TrkB-mediated IP3 formation (23) and subsequent calcium release from intracellular stores (21,23). This positive feedback might persist until counterregulatory mechanisms come into play, such as internalization of TrkB receptors and͞or a reduction of BDNF secretion induced by nitric oxide3protein kinase G signaling (30).…”
Section: Discussionsupporting
confidence: 70%
“…A comparable rate of decrease in BDNF concentrations was observed in the absence of electrical stimulation (to 94 Ϯ 3% after 20 min and to 82 Ϯ 2% after 100 min; data not shown), indicating that endogenous BDNF secretion occurs spontaneously from the slice preparation. Basal release of endogenous BDNF, analyzed previously in hippocampal neurons (19,21,22,30), results from combined ''constitutive'' and ''regulated'' secretion. The regulated component of this pathway is an activity-dependent process that includes both stimulatory and inhibitory signals (30).…”
Section: Bdnf Expression In Prh Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Canossa et al (2002) reported in studies with cultured embryonic hippocampal neurons that L-N--nitro-L-arginine methyl ester, a nonspecific NOS inhibitor, increased BDNF secretion, and an NO donor decreased BDNF secretion. In contrast to our in vivo studies in adult cerebral tissue, their studies were performed in vitro with embryonic cells.…”
Section: Molecular Mechanism Underlying Enos Regulation Neurogenesismentioning
confidence: 99%
“…Recent studies show that NO regulates BDNF expression, which affects neural progenitor cell proliferation and differentiation in the mammalian brain (Canossa et al, 2002;Cheng et al, 2003). NO mediates BDNFinduced growth-associated protein 43 (GAP-43) mRNA expression (Klocker et al, 2001).…”
Section: Introductionmentioning
confidence: 99%